2018
DOI: 10.1016/j.pharep.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition on angiotensin-converting enzyme exerts beneficial effects on trabecular bone in orchidectomized mice

Abstract: The inhibition on ACE by captopril exerts beneficial effects on trabecular bone of ORX mice. The therapeutic efficacy may be attributed to the regulation of captopril on local RAS and cytokines in bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Both issues warrant further exploration. It is tempting to speculate that the renin/angiotensin/aldosterone axis might be involved, as well (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Both issues warrant further exploration. It is tempting to speculate that the renin/angiotensin/aldosterone axis might be involved, as well (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Also, coadministration of estradiol and ramipril were superior to administration of each of them alone in both increase of serum RANKL and decrease of serum OPG. Also, Chen et al (24) reported that the administration with captopril in orchidectomized mice for six weeks enhanced the ratio of OPG/RANKL mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of RAAS inhibitors were also reported in many studies. The mice with bilateral orchiectomy may have a significantly increased trabecular bone area after the treatment of captopril [ 38 ]. Similarly, another animal study also proved that imidapril treatment may reduce the decrease of bone density and inhibit the increase in osteoclast activation in rats with ovariectomy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%